Codigestion of high pressure thermal hydrolysis‐treated thickened waste activated sludge with primary sludge in two‐stage anaerobic digestion. Issue 1 (28th September 2017) - Sarwar, Rubaiya; Elbeshbishy, Elsayed; Parker, Wayne J.
Abstract : Pretreatment of thickened waste activated sludge (TWAS) with high pressure thermal hydrolysis (HPTH) prior to co‐digestion with primary sludge (PS) in two‐stage anaerobic digestion was evaluated at two systems hydraulic residence times (HRTs). Pretreatment increased the soluble COD (SCOD) entering the acidogenic digester and at a 2 day HRT the increase in SCOD through the digester was also enhanced. With a 1 day HRT in the acidogenic digester the increment in SCOD concentrations was smaller in the pretreated reactor than in the control reactor suggesting there is a minimum residence time required to maintain hydrolysis of pretreated TWAS. At the 2 day HRT fermentation to volatile fatty acids (VFA) was similar in both reactors despite the considerably higher SCOD concentrations in the pretreated sludge. In contrast, at the 1 day HRT the pretreated digester VFA concentrations were 36% higher than that of the control digester. The control and pretreated methanogenic digesters operating at an HRT of 13 days had average total COD (TCOD) removal efficiencies of 45 and 52%, respectively which was consistent with an increase in methane yield from 0.19 L CH4 /g COD for the control system to 0.23 L CH4 /g COD for the pretreated system. With an HRT of 9 days, the corresponding TCOD removal efficiencies were reduced to 43% in and 48% respectively and the methane yields were 0.14 and 0.16 L CH4 /g COD, respectively. COD removal to methane was found to be not significantly different between the control and pretreated systems at the reduced HRT. © 2017 American Institute of Chemical Engineers Environ Prog, 37: 425–433, 2018